The Effect of Compensation and Work Discipline on Employee Productivity of Pt. Indofood Sukses Makmur Tbk Jakarta - Naufal Hafif Hasibuan (Maneggio, 2024)
The benchmark of organizational success in carrying out management can be reviewed from the management of human resources which is shown based on the maximum productivity of employees. Increasing employee productivity can be realized by providing compensation and improving employee discipline. This study aims to find out the application of employee compensation and work discipline affects the productivity of employees of PT. Indofood Sukses Makmur Tbk Jakarta. The research sample was determined by simple random sampling which resulted in 171 respondents from the entire employee population at PT. Indofood Sukses Makmur Tbk Jakarta with data collection through questionnaires. This study uses the multiple linear regression method to determine the influence between dependent variables and independent variables. Based on the results of the analysis conducted in the study, it is known that compensationand work discipline have a positive and partially significant influence on employee work productivity. Providing high compensation or in accordance with employee needs can stimulate employee productivity at work. Increasing productivity must also be accompanied by increasing employee discipline through policies or rules in the form of sanctions to reduce the number of employee discipline, so that employee productivity can be provided optimally.